Graded band-gap engineering for increased efficiency in CZTS solar cells, ISSN / e-ISSN 0925-3467 / 1873-1252 - Hichem, Ferhati; DJEFFAL Fayçal (Optical MaterialsOptical Materials, 2018)
In this paper, we propose a potential high efficiency Cu2ZnSn(S,Se)4/CdS (CZTS) solar cell design based on graded band-gap engineering that can offer the benefits of improved absorption behavior and reduced recombination effects. Moreover, a new hybrid approach based on analytical modeling and Particle Swarm Optimization (PSO) is proposed to determinate the optimal band-gap profile of the amended CZTS absorber layer to achieve further efficiency enhancement. It is found that the proposed design exhibits superior performance, where a high efficiency of 16.9% is recorded for the optimized solar cell with a relative improvement of 92%, compared with the reference cell efficiency of 8.8%. Likewise, the optimized CZTS solar cell with a graded band-gap enables achieving a higher open circuit voltage of 889 mV, a short-circuit current of 28.5 mA and a fill factor of 66%. Therefore, the optimized CZTS-based solar cell with graded-band gap paradigm pinpoints a new path toward recording high-efficiency thin-film solar cells through enhancing carrier collection and reducing the recombination rate.